Edupreneurship in Stimulating the Independence of Early Childhood - Ismaiyah, Nurul; Suyadi, Suyadi; Nadlifah, Nadlifah; Putro, Khamim Zarkasih; Astuti, Ria (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2022)
Purpose – This study aims to analyze the role of edupreneurship in training children's independence. This study describes the strategies undertaken to stimulate children's independence values through several entrepreneurial activities such as market day activities, cooking classes and work bazaars.Design/methods/approach – This research method is qualitative descriptive. The research subject is the principal, an early childhood education class teacher in Batu Karang who implements edupreneur day. This research was conducted in Batu Karang Village. Data were collected through observation, interviews and documentation to obtain in-depth information. The type of interview chosen was semi-structured. Conclusions are obtained from the results of data analysis with three stages reduction, data display and then conclusion. Test the validity of the data is done through source and technique triangulation.Findings – The study found that many children were still less orderly, disciplined and dared to carry out activities independently. This research shows the role of edupreneurship in stimulating independence from an early age through entrepreneurial activities.Research implications/limitations – Market day activities have implications for training children from an early age to be independent so that the child's perspective will rise to become an entrepreneur. This study has limitations in learning early childhood education in rural areas that are not promoted independently, so the activities carried out are not monitored.Practical implications – This study implies that edupreneurship in training early childhood independence can be done through market day activities.Originality/value – This study contributes to understanding teachers and education parties utilizing entrepreneurial activities to foster an independent spirit for entrepreneurship and building the economy. Paper type: Research paper